Improving Farmers Capability Through Local Potencies in Wukir Sawit Village, Jatiyoso Subdistrict, Karanganyar - Zuhri, Saifuddin (Universitas Negeri Medan, 2022)
The aim of this study is to know the empowerment process conducted by Himpunan Tani Ngudi Makmur (HTNM) in improving Jatiyoso farmers capability through local resources. The research method used in this study is qualitative descriptive. The research result shows that Jatiyoso farmers took the initiative to form Himpunan Tani Ngudi Makmur (HTNM) as organization which trying to increase the independence of farmers and improving agricultural technology that is environmentally friendly and can improve the standard of living of farmers. One of the innovation that improved in Jatiyoso is cassava processing into Modified Cassava Flour (Mocaf) as wheat flour substitute. This Mocaf processing involving farmers and is expected to increase the economic value of cassava.